2018
DOI: 10.3390/ma11030412
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide Stress Cracking Behavior of a Martensitic Steel Controlled by Tempering Temperature

Abstract: A medium-carbon Cr–Mo–V martensitic steel was thermally processed by quenching (Q) at 890 °C and tempering (T) at increasing temperatures from 650 °C to 720 °C and the effect of tempering temperature, Tt, on sulfide stress cracking (SSC) behaviors was estimated mainly via double cantilever beam (DCB) and electrochemical hydrogen permeation (EHP) tests and microstructure characterization. The results indicate that the threshold stress intensity factor for SSC, KISSC, increased with increasing Tt. The overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…При этом в данной области также обнаружили участки с повышенным содержанием мартенсит/аустенитной составляющей неправильной формы. В области излома наблюдаются многочисленные вторичные микротрещины, поскольку мартенситная структура менее устойчива к СРН и требует дополнительного отпуска [21].…”
Section: обсуждение результатовunclassified
“…При этом в данной области также обнаружили участки с повышенным содержанием мартенсит/аустенитной составляющей неправильной формы. В области излома наблюдаются многочисленные вторичные микротрещины, поскольку мартенситная структура менее устойчива к СРН и требует дополнительного отпуска [21].…”
Section: обсуждение результатовunclassified
“…Sun et al [ 19 ] proposed that the relationship between the size of grain boundaries and the density of hydrogen traps ( N false) $N \left.\right)$ can be equated using (Equation ()) N = n S G x GB 2 n V G x a 3 $$N = \frac{n S_{\text{G}} x_{\text{GB}}}{2 n V_{\text{G}} x_{\text{a}} ^{3}}$$ where: n is the number of grains counted per m 3 and S G $a n d S_{\text{G}}$ and V G $V_{\text{G}}$ are the surface area and volume of a grain; the width of grain boundaries ( x GB $x_{\text{GB}}$ ) such as PAG, packets, blocks, and laths can be assumed to be 10 times the distance between two atoms ( x a $x_{\text{a}}$ ); the ratio between the dislocation density ( ρ Dis $\left(\rho\right)_{\text{Dis}}$ ) and x a $x_{\text{a}}$ was assumed to be 5:1 for the same N in the same microstructure. [ 19 ] In light of this, Bai et al [ 80 ] suggested that smaller grains would have less dislocation pile‐up when compared to larger grains, therefore reducing localized accumulation of hydrogen concentration at grain boundaries.…”
Section: Microstructure Constituents Influencing Sscmentioning
confidence: 99%
“…[16,17] The initiation and propagation of SSC at these PAG boundaries is not only affected by the size of PAGs or type of element that partitioned to these boundaries, but also the type of microstructure constituent that nucleates from these boundaries. [18][19][20][21] Hence, the following sections will highlight and discuss different microstructure constituents of interests within PAG in relevance to their contribution to SSC. This section will briefly review the types of microstructures of interest commonly found in low-carbon TMCP pipeline steels.…”
Section: Types Of Tmcp Microstructures' Constituentsmentioning
confidence: 99%
See 2 more Smart Citations